Assessment of the unique nutrient contribution of white potatoes in the diet and the nutrient implications of replacing Refined and Whole Grains with Starchy Vegetables - Richter, Chesney; Fulgoni, Kristin; Fulgoni, Victor L.; Johnson, Bonnie; Kijek, Michelle; Maniscalco, Shelley; Psota, Tricia (Frontiers in Nutrition, 2025)
BackgroundPotatoes are a versatile and naturally nutrient-dense vegetable that contain many nutrients, including fiber, potassium, and vitamins C and B6. The 2025 Dietary Guidelines Advisory Committee (DGAC) considered changes to the Vegetable subgroups and potential interchangeability of Grains and Starchy Vegetables. This modeling analysis was conducted to quantify the nutrient contribution of white potatoes and Starchy Vegetables compared to Refined and Whole Grains.MethodsThe objectives from the 2025–2030 DGAC protocol “What are the implications for nutrient intakes when modifying the quantities of the Grains group within the Healthy U.S.-Dietary Pattern” were modeled using the 2025 DGAC Staple Carbohydrate Foods Food Pattern Modeling (FPM) protocol and the 2020 DGAC FPM analyses. The modeling focused on women aged 19–30 years of age and men aged 51 + years of age to match the 2,000-calorie level widely used in dietary recommendations.ResultsThe recommended daily serving of white potatoes (0.58 cup equivalents) provides 11% of daily potassium and 6% of daily fiber, as well as vitamins B6 and C, copper, magnesium, thiamin, and niacin. White potatoes are currently underconsumed, while the current intake of Other Starchy Vegetables (e.g., corn, green peas, and plantains) nearly meets the recommended amount. Replacing Refined Grains with Starchy Vegetables increases fiber, potassium, vitamin C, and choline intake but decreases other nutrients such as iron, folate, and riboflavin. Replacing Whole Grains with Starchy Vegetables similarly increases potassium, vitamin C, and choline but decreases the intake of fiber, calcium, iron, magnesium, folate, and other vitamins.ConclusionThese results provide insight into the unique nutritional contribution of white potatoes and demonstrate that Starchy Vegetables and Grains are not interchangeable in dietary patterns based on their unique nutritional packages. Therefore, reducing the recommended intake of Starchy Vegetables may be counterproductive for improving diet quality.